The dark side of Tregs during aging - Palatella, Martina; Guillaume, Stephane M.; Linterman, Michelle A.; Huehn, Jochen (Frontiers in Immunology, 2022)
In the last century, we have seen a dramatic rise in the number of older persons globally, a trend known as the grey (or silver) tsunami. People live markedly longer than their predecessors worldwide, due to remarkable changes in their lifestyle and in progresses made by modern medicine. However, the older we become, the more susceptible we are to a series of age-related pathologies, including infections, cancers, autoimmune diseases, and multi-morbidities. Therefore, a key challenge for our modern societies is how to cope with this fragile portion of the population, so that everybody could have the opportunity to live a long and healthy life. From a holistic point of view, aging results from the progressive decline of various systems. Among them, the distinctive age-dependent changes in the immune system contribute to the enhanced frailty of the elderly. One of these affects a population of lymphocytes, known as regulatory T cells (Tregs), as accumulating evidence suggest that there is a significant increase in the frequency of these cells in secondary lymphoid organs (SLOs) of aged animals. Although there are still discrepancies in the literature about modifications to their functional properties during aging, mounting evidence suggests a detrimental role for Tregs in the elderly in the context of bacterial and viral infections by suppressing immune responses against non-self-antigens. Interestingly, Tregs seem to also contribute to the reduced effectiveness of immunizations against many pathogens by limiting the production of vaccine-induced protective antibodies. In this review, we will analyze the current state of understandings about the role of Tregs in acute and chronic infections as well as in vaccination response in both humans and mice. Lastly, we provide an overview of current strategies for Treg modulation with potential future applications to improve the effectiveness of vaccines in older individuals.